Morpho-phylogenic characterization of Neonectria candida as a causal agent of a postharvest rot of pome fruit in the U.S. Pacific Northwest - Mellow, Joseph K.; Arifin, Arild R.; Amiri, Achour (Frontiers in Plant Science, 2025)
Neonectria fruit rot (NFR) is primarily attributed to Neonectria ditissima, the causal agent of European canker, in many apple-growing regions globally. Between 2017 and 2019, NFR-like symptoms were observed in several surveyed apple and pear packinghouses in Washington State and Oregon. In this study, 52 Neonectria isolates were characterized using a multilocus sequence analysis (MLSA), pathogenicity assays, and morphological traits across various growth media and photoperiods. MLSA analysis of four DNA regions, i.e., β-TUB, TEF1, LSU, and ITS rDNA, identified the pathogen as Neonectria candida (syn. Neonectria ramulariae, anamorph Cylindrocarpon obtusiusculum). All the 52 N. candida isolates formed a distinct clade from N. ditissima and other Neonectria spp. with a Bayesian interference posterior probability of 0.98. Fruit pathogenicity assays showed that N. candida isolates caused light brown lesions on ‘Fuji’ apples and ‘Green d’Anjou’ pears both at room temperature (22°C) and cold storage (0.5 and 1.5°C), with NFR incidences ranging from 6 to 100% after 15 days to four months. N. candida isolates grew and sporulated profusely under a multitude of nutrient and photoperiod conditions in vitro. This study is a foundational step towards species identification and understanding the biology and epidemiology of NFR to support the development of effective management approaches.